Arts Sector Research in Development: Participant Perspectives on a Community-Engaged Research Initiative - Gamble, Jamie; Nelson, Robin (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2023)
Despite good intentions, academic research often reflects an extractive model and is not always seen as useful within the Canadian arts sector. Mass Culture is a non-profit organization that aims to bring together cultural workers and academics in support of collaborative research and better knowledge mobilization. To that end, their Research in Residence (RinR) initiative involved complex collaborations between the arts sector and academia to explore five applied research projects on a topic of shared importance to participants - that is, articulating the value of the arts through qualitative rather than quantitative measurements. To learn from the experimental research design, participants conducted a developmental evaluation with five lines of inquiry: benefits and effects, program design adaptations, values alignment, efficacy and potential, and knowledge mobilization and research engagement. The evaluation had three purposes: (1) to gather data and facilitate analysis of the key questions that the initiative was trying to understand; (2) to inform Mass Culture's implementation and adaptation of the initiative; and (3) to generate insights on principles and practices that could inform the design of future initiatives. This article considers the second and third purposes, outlining key lessons learned that shaped the initiative and/or should inform future projects.